Use of continuous subcutaneous insulin infusion versus multiple daily injections in emerging adults with type 1 diabetes is associated with better clinical engagement but not glycaemic control. Issue 2 (22nd July 2022) - Chai, Thora Y. L.; Farrell, Kaye; Holmes‐Walker, Deborah J.
Abstract: Background: Limited studies have compared outcomes between emerging adults with type 1 diabetes mellitus (T1D) attending a diabetes transition support programme using multiple daily injections (MDI) or continuous subcutaneous insulin infusion (CSII). Aims: To assess glycaemic control and service utilisation in emerging adults with T1D on MDI or CSII attending a young adult diabetes clinic (YAC). Methods: A retrospective cohort analysis was conducted from January 2013 to December 2015. Data collected included clinic visits per year, after‐hours mobile telephone use, diabetic ketoacidosis (DKA) admissions and all HbA1c levels. Independent t ‐test was used to compare continuous variables whilst Pearson's Chi‐squared test was used for categorical variables. Linear mixed effects models explored mean changes in HbA1c levels over time. Results: Over 3 years, 318 youth with T1D (176 MDI, 121 CSII, 21 switched from MDI to CSII) attended our YAC. Aggregated mean HbA1c levels remained similar between modalities (CSII 9.1% vs MDI 9.3%; P = 0.23); however, mean change in HbA1c at 3 years was significantly increased in CSII users at 0.55% (95% CI 0.15–0.95; P < 0.01) compared with no significant change in MDI users. Clinic visits per year were improved in CSII users (CSII 2.8 vs MDI 2.5; P = 0.02), while DKA admissions remained similar between MDI and CSII users (3.6 admissions per 100 patient‐years). Conclusion: In our YAC cohort, glycaemic control in CSII and MDI users was similar but well below recommended international glycaemic targets (HbA1c level < 7.0%). Despite increased clinical engagement occurring in CSII users, glycaemic deterioration was observed over the 3 years.